Hydrologic and Agricultural Earth Observations and Modeling for the Water-Food Nexus - McNally, Amy; McCartney, Sean; Ruane, Alex C.; Mladenova, Iliana E.; Whitcraft, Alyssa K.; Becker-Reshef, Inbal; Bolten, John D.; Peters-Lidard, Christa D.; Rosenzweig, Cynthia; Uz, Stephanie Schollaert (Frontiers in Environmental Science, 2019)
In a globalizing and rapidly-developing world, reliable, sustainable access to water and food are inextricably linked to each other and basic human rights. Achieving security and sustainability in both requires recognition of these linkages, as well as continued innovations in both science and policy. We present case studies of how Earth observations are being used in applications at the nexus of water and food security: crop monitoring in support of G20 global market assessments, water stress early warning for USAID, soil moisture monitoring for USDA’s Foreign Agricultural Service, and identifying food security vulnerabilities for climate change assessments for the UN and UK international development agency. These case studies demonstrate that Earth observations are essential for providing the data and scalability to monitor relevant indicators across space and time, as well as understanding agriculture, the hydrological cycle, and the water-food nexus. The described projects follow the guidelines for co-developing useable knowledge for sustainable development policy. We show how working closely with stakeholders is essential for transforming NASA Earth observations into accurate, timely, and relevant information for water-food nexus decision support. We conclude with recommendations for continued efforts in using Earth observations for addressing the water-food nexus and the need to incorporate the role of energy for improved food and water security assessments.